Estimasi Pertumbuhan Investasi Sukuk dalam Pencapaian Sustainable Development Goals (SDGs) di Indonesia - Nasution, Adinda Maharani; Rasyid, Arbanur; Lubis, Rukiah (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the best model and method for forecasting the growth of sukuk investment in Indonesia and to forecast the growth of Sovereign Sukuk investment seven years ahead, precisely at the end of the Sustainable Development Goals (SDGs) program in 2030. This quantitative study uses Sovereign Sukuk data from 2009 to 2023 obtained from Bank Indonesia (BI). The sampling technique used in this study is purposive sampling, which uses 179 monthly data on Indonesian Sovereign Sukuk investment. The data analysis in this study uses the eviews 10 application with an econometric approach. The results of this study analysis show that the best method for forecasting sukuk investment growth in Indonesia is ARIMA Box Jenskins with the ARIMA (7,1,1) model. The growth value of Indonesian Sovereign Sukuk investment after forecasting for the next seven years continues to increase yearly. This is triggered by the increasing public awareness to contribute to Indonesia's development. The peak growth in Sovereign Sukuk investment is predicted to occur in 2030 at the end of the Sustainable Development Goals (SDGs) agenda, showing a figure of Rp. 1.167.071.086.806.520. This condition should be a concern to the government, so that Sovereign Sukuk can be utilised to achieve the Sustainable Development Goals (SDGs) program in Indonesia.